Priority Infrastructure Development on Tablolong Beach Tourism Kupang Regency - East Nusa Tenggara - Johannis, Dian Erlina Wati; Trisnoyuwono, Diarto; Mata, Abia E. (International Journal of Offshore and Coastal Engineering (IJOCE), 2023)
The Tablolong beach area is one of the natural tourism objects in Kupang Regency. However, it is not matched by adequate tourist area infrastructure. This study aims to analyze the required infrastructure to assess the existing condition of infrastructure in the Tablolong beach area using a qualitative descriptive analysis, analyzing the IPA (Importance-Performance Analysis) level of importance of infrastructure in tourist areas and providing recommendations for infrastructure development directions. The results of the study indicate that the priority infrastructure developed to support the fisheries and trade services sector are 1) provision of domestic waste management facilities (laundry waste and toilets), provision of a clean water network system, provision of waste disposal sites; 2) handling potholes in road conditions and asphalting of roads that are still pavement; 3) provision of various modes of transportation and drainage systems, especially in fishing settlements and beaches; 4) provision of transportation support facilities, improvement of telecommunications performance, improvement of electricity network performance in the Tablolong Beach area under the development of the area.